Revising Complex Supramolecular Polymerization under Kinetic and Thermodynamic Control - Matern, Jonas (Angew Chem Int Ed Engl, 2019)
Pathway complexity, hierarchical organization, out of equilibrium, and metastable or kinetically trapped species are common terms widely used in recent, high‐quality publications in the field of supramolecular polymers. Often, the terminologies used to describe the different self‐assembly pathways, the species involved, as well as their relationship and relative stability are not trivial. Different terms and classifications are commonly found in the literature, however, in many cases, without clear definitions or guidelines on how to use them and how to determine them experimentally. The aim of this Minireview is to classify, differentiate, and correlate the existing concepts with the help of recent literature reports to provide the reader with a general insight into thermodynamic and kinetic aspects of complex supramolecular polymerization processes. A good comprehension of these terms and concepts should contribute to the development of new complex, functional materials.